USER EDUCATION DI PERPUSTAKAN SMKN 1 PERHENTIAN RAJA - Vita Amelia; Adrian Aery Lovian (LPPM Universitas Bina Bangsa, 2024)
User education or known as user education is an initial activity for library users This service activity aims to make students and students at SMK Negeri 1 Perhentian Raja know how to use and utilize the library properly through user education. This user education program can then be implemented in the school library. The method used in this service is survey and direct practice in the library of SMKN 1 Perhentian Raja. This method is used with the aim of getting a comprehensive picture of how an activity is carried out. The results of the service show that the SMK Negeri 1 Perhentian Raja Library has been established for a long time but has not yet carried out user education activities for its students. Therefore, the team conducted user education activities in the library by creating a user education program and practicing the materials in the program. Many students expressed that user education activities are very positive and beneficial for them; this can be seen from the changes in knowledge obtained from pre and post tests